2022
DOI: 10.1111/cea.14207
|View full text |Cite
|
Sign up to set email alerts
|

Paediatric asthma and non‐allergic comorbidities: A review of current risk and proposed mechanisms

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 145 publications
0
3
0
Order By: Relevance
“…It has also been consistently shown that maternal psychological stress during pregnancy and postpartum is associated with psychological and psychiatric issues in children up to the age of 21 years 6,7 . Finally, children with asthma and allergic disease are more likely to have co‐occurring internalizing disorders (depression and anxiety), and there is some evidence to suggest that a common shared environmental factor may be in part responsible 8–11 . In this study we propose that maternal mental health disorders may be the common shared factor.…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“…It has also been consistently shown that maternal psychological stress during pregnancy and postpartum is associated with psychological and psychiatric issues in children up to the age of 21 years 6,7 . Finally, children with asthma and allergic disease are more likely to have co‐occurring internalizing disorders (depression and anxiety), and there is some evidence to suggest that a common shared environmental factor may be in part responsible 8–11 . In this study we propose that maternal mental health disorders may be the common shared factor.…”
Section: Introductionmentioning
confidence: 68%
“…6,7 Finally, children with asthma and allergic disease are more likely to have co-occurring internalizing disorders (depression and anxiety), and there is some evidence to suggest that a common shared environmental factor may be in part responsible. [8][9][10][11] In this study we propose that maternal mental health disorders may be the common shared factor. Supporting this theory, a study by Brehm et al found that the association between child psychological stress and asthma was greater in mothers who were stressed in pregnancy, compared to those who were not, 12 and another study found that children treated for depression with mothers who also had depression, were more likely to have asthma compared to children whose mothers did not have depression.…”
Section: Backg Rou N Dmentioning
confidence: 91%
“…Firstly, asthma, anxiety, and depression are heterogeneous, with correlations influenced by various factors like gender and age; for example, females with severe asthma often tend to have higher rates of anxiety and depression than males ( 47 ). Additionally, the bidirectional relationship between depression, anxiety, and asthma not only exists in adults but also extends to children with asthma ( 48 ). Our understanding is still limited, which necessitates future studies with larger sample sizes to conduct more detailed subgroup analysis of these diseases.…”
Section: Discussionmentioning
confidence: 99%
“…The mean Asthma Control Test score (ACT) was 17 ± 5, mean mini-Asthma Quality of Life Questionnaire score (mini-AQLQ) was 4.23 ± 1.15, and median exacerbation rate the past 1 year was 3 (1-5). All patients had at least 1 treatable trait and a median of four traits (3)(4)(5)(6). The prevalence of pulmonary, extrapulmonary and behavioural traits was 86.5%, 85.7% and 57.9%, respectively.…”
Section: R S E a R C H L E T T E R Treatable Traits In An Asian Diffi...mentioning
confidence: 99%